Meningkatkan Kualitas SDM Untuk Mencapai Keunggulan Kompetitif Perusahaan di Era Digital: Tren, Inovasi, dan Tantangan - Guruh Suksmono Aji; Iva Khoiril Mala (Jurnal Manajemen dan Ekonomi Kreatif, 2024)
To face the challenges of globalization and digital change, companies must focus on improving the quality of their workforce through training and HR development efforts. This is a crucial step in achieving competitive advantage in an ever-changing market Successful training is not just about improving technical skills, but also building a responsive and creative organizational culture. Quality human resources are identified as the main key in facing the challenges of changing dynamic business environments. This research uses literature analysis methods to examine various innovative strategies in developing HR training programs, including the use of AI and VR technology, microlearning and blended learning approaches, and the implementation of gamification. Proactive investment in training programs that are relevant to needs will have a significant impact in increasing company efficiency, productivity, innovation and adaptation to changes in the business environment. Therefore, the aim of this research is to provide comprehensive insight into the importance of investment in training and development of human resources (HR). It is hoped that by emphasizing improving the quality of human resources and continuity of training programs, companies can achieve and maintain their competitive advantage in the long term.